Identification of Student Misconception on Reduction-Oxidation Reactions using The Four Tier Diagnostic Test Instrument - Vera Dwi Alfina, Vera; Sura Menda Ginting; I Nyoman Candra (University of Bengkulu, 2024)
This research aims to identify students' misconceptions on redox reaction material using the Four Tiers Diagnostics Test. The four tiers/stages are selecting answer, affirmation of the chosen answer, selecting reason of the chosen answer, and the affirmation of the selected reason. The diagnostic was carried out at SMAN (senior high school) 5 Bengkulu. The trial of the diagnostic test was conducted to students of class X MIPA 3 and the misconception diagnostic was conducted to students of X MIPA 2. The results show that the percentage of student misconceptions regarding the redox reaction material was 35% (medium category), while 40% of students understand the concept, and 25% of students do not understand the concept. The highest misconception occurs in the sub-concept of reduction and oxidation reactions (42%), follows by dispropornation and conpropornation reactions, (38%), oxidizing-reducing agents (37%), change in oxidation number from element to compound (24 %).